The Role of Greenpeace Netherlands in Advocating the Bonaire’s Plight amidst the Threat of Climate Change - Manullang, Abel Josafat; Alfi, Raihan (HAPSc Policy Briefs Series, 2024)
Climate change has grown to become a global threat towards the international community. For that, states have made the move to mitigate and overcome it either through unilateral or multilateral means. One state in particular engages in both means, that being the Netherlands. While it is true that it has taken some strides in facing climate change, it appears to not be adequate as to encompass its special municipality in the Caribbean, that being Bonaire. Recently, a new actor has stepped in to demand the government to make adequate efforts to support Bonaire in facing climate change. Such a feat was done through making a lawsuit against the Dutch state back in early 2024. The new actor is an environmental non-governmental organization (NGO) known as Greenpeace, specifically Greenpeace Netherlands. Through employing the qualitative research method, the article seeks to explain the role of Greenpeace Netherlands as an environmental NGO in its recent lawsuit against the Dutch state. Said analysis is further strengthened by the conceptual framework of environmental NGOs strategies by McCormick. The article finds how as an environmental NGO, Greenpeace Netherlands carried out its role, among others, through campaigning and organizing public protests as well as undertaking research.